Alwaqf (Endowment) as a Basis for Islamic Takaful Insurance, between Theory and Practice - Al-Oqaili, Amenah; Al-Jbour, Fadi; Maabdeh , Zainab (Dirasat: Shari'a and Law Sciences, 2021)
This research aims to determine the extent to which the endowment can be applied in the Takaful insurance companies and to explain the ruling on Takaful insurance, which made some agree on the permissibility of Takaful insurance while others outlawed it. The research sheds light on the endowment and its pioneering role in building Islamic Takaful insurance institutions, highlighting a legitimate vision capable of employing the endowment in the field of Takaful insurance and being able to compete with the commercial insurance companies by meeting the needs of society and reducing risks facing society. This research is based on inductive, descriptive, and comparative methods. This research is divided into four sections. First, it defines the endowment in language and idiom, its types, legality, and its pillars. Second, it defines Takaful insurance, the opinions of the jurists, their evidence, and its objectives, and the difference between Takaful insurance and commercial insurance. Third, it mentions the reasons for building Takaful insurance. Fourth, establishing based on insurance on the basis of the endowment, in addition to providing contemporary applied models. The research concluded that Islamic Takaful insurance is based on cooperation and advocacy, and it is legal to establish an endowment on its basis. The research recommended that Islamic insurance companies benefit from the experiences of Islamic insurance companies based on the endowment.